Pengaruh Kompensasi Kerja terhadap Kinerja Pegawai di Sebuah Perguruan Tinggi Swasta Kota Bandung - Yudhistira Anugerah Pratama; Farida Yulianty; Kosasih Kosasih (TECHNO-SOCIO EKONOMIKA, 2026)
This study analyzes the effect of work compensation on employee performance at a private university in Bandung. Compensation includes wages, benefits, positions, and facilities. A mixed-method with concurrent nested design was employed. Using Slovin formula with 10% error margin, 76 respondents were selected. Data were collected through interviews, questionnaires, and secondary sources. Results showed compensation was well-implemented (total score: 2,198). Multiple linear regression revealed significant positive effects of compensation on performance (R² = 0.654, p < 0.05). Wages (β = 0.312), benefits (β = 0.298), and facilities (β = 0.284) significantly influenced performance, while position showed no significant effect (β = 0.089, p > 0.05). Effective compensation enhances employee performance, contributing to institutional reputation and operational sustainability.